2019
DOI: 10.3314/mmj.19.001
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Feline and Canine Dermatophytoses in Japan

Abstract: In a 2012-2014 epidemiological study of feline and canine dermatophytoses in Japan, we investigated the prevalence of fungi among 296 cats and 170 dogs treated at a veterinary clinic and 51 cats and dogs at an animal shelter at Fukui City in Japan. Microsporum canis was isolated from only one cat out of the 517 animals. Also, from 2012 to 2017, we analyzed isolates from 76 cats and 15 dogs with dermatophytoses at 14 veterinary clinics across 10 prefectures in Honshu and Shikoku. M. canis was the cause for 85 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
6
20
0
Order By: Relevance
“…A higher isolation rate was detected mainly from outdoor dogs and cats that were reared in pet animal facilities (41.17 and 32.72%) than household ones (9.37 and 8.8%) respectively, as denoted in Table 3. Such obtained data was parallel to that achieved by Copetti et al (2006) and Yamada et al (2019), which implies that outdoor transmission acted as a major infection route for ringworm. This could be referred to the unsanitary conditions as well as the high stocking density in such places, as well as the fungal spores cross contamination between healthy animals and diseased ones with skin mycosis which confirms the natural route of dermatophyte infection especially with M. canis as assumed by Minnat and Khalaf (2019).…”
Section: Resultssupporting
confidence: 74%
“…A higher isolation rate was detected mainly from outdoor dogs and cats that were reared in pet animal facilities (41.17 and 32.72%) than household ones (9.37 and 8.8%) respectively, as denoted in Table 3. Such obtained data was parallel to that achieved by Copetti et al (2006) and Yamada et al (2019), which implies that outdoor transmission acted as a major infection route for ringworm. This could be referred to the unsanitary conditions as well as the high stocking density in such places, as well as the fungal spores cross contamination between healthy animals and diseased ones with skin mycosis which confirms the natural route of dermatophyte infection especially with M. canis as assumed by Minnat and Khalaf (2019).…”
Section: Resultssupporting
confidence: 74%
“…In a survey of a few hundred cats and dogs from households, shelters, pet shops, or stray, conducted by Yamada et al (2019) in Japan, M. canis was absent or had a very low prevalence (1.1-3%) in the surveyed areas. The fungus was, however, more prevalent (21.5%) in cats in animal raising establishments.…”
Section: Urban Areasmentioning
confidence: 99%
“…Our recent epidemiological studies of dermatophytosis of pet animals in Japan (9,10) showed that M. canis was the most prevalent causative fungus in both cats and dogs. In cats, there are two major reservoirs of the fungus: pet shops and commercial breeding facilities (PS), and stray cats and pet cats that go outdoors and come in contact with stray cats (Outdoor).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…In cats, there are two major reservoirs of the fungus: pet shops and commercial breeding facilities (PS), and stray cats and pet cats that go outdoors and come in contact with stray cats (Outdoor). In dogs, there is only one reservoir, the PS route (10). However, the infection status of the fungus among the reservoirs and risk of contagion to humans are still unclear.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
See 1 more Smart Citation